Inhibitory Activity of Food-originated Pediococcus pentosaceus NP6 Against Salmonella enterica serovar Typhimurium in Nile Tilapia By-products - Siriyanapat Tasaku (Science Faculty of Chiang Mai University, 2019)
Pediococcus pentosaceus NP6 is a potent probiotic bacterial strain isolated from a traditional Thai fermented fish or nam-pla (fish paste). This strain exhibits antibacterial activities against several important food-borne pathogens (both Gram-positive and Gram-negative species), including Salmonella enterica serovar Typhimurium ATCC13311. Strain NP6 also has several advantageous properties, including tolerance to salt, acid, and bile salt and the abilities to use a wide range of carbohydrates and to produce extracellular lipase and amylase. To investigate their potentials as bioactive agents for raw meat preservation, single inoculum of NP6 and S. Typhimurium cell suspensions were individually inoculated into fresh Nile tilapia by-products, including meat, belly flap meat and skin. All bacterial strains were able to multiply, although NP6 exhibited better growth in all tilapia samples. Following co-inoculation of P. pentosaceus NP6 and S. Typhimurium, NP6 predominated over S. Typhimurium, which exhibited a significantly reduced abundance. Therefore, the efficacy of P. pentosaceus NP6 for controlling several food-borne pathogens makes this strain a promising bioprotective agent for preserving raw meat that delays the growth of pathogenic microorganisms during storage.